Structure of poly(L-lactic acid)s prepared by the dehydropolycondensation of L-lactic acid with organotin catalysts - Shyamroy, S.; Garnaik, Baijayantimala; Sivaram, S. (Journal of Polymer Science Part A-Polymer Chemistry, 2005)
The synthesis of low-molecular-weight (weight-average molecular weight < 45,000 g/mol) lactic acid polymers through the dehydropolycondensation of L-lactic acid was investigated. Polymerizations were carried out in solution with solvents (xylene, mesitylene, and decalin), without a solvent using different Lewis acid catalysts (tetraphenyl tin and tetra-n-butyldichlorodistannoxane), and at three different polymerization temperatures (143, 165, and 190 degrees C). The products were characterized with differential scanning calorimetry, size exclusion chromatography, vapor pressure osmometry, C-13 NMR, and matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF). The resulting polymers contained less than 1 mol % lactide, as shown by NMR. The number-average molecular weights were calculated from the ratio of the area peaks of ester carbonyl and carboxylic acid end groups via C-13 NMR. The stereosequences were analyzed by C-13 NMR spectroscopy on the basis of triad effects. Tetraphenyl tin was an effective transesterification catalyst, and the randomization of the stereosequence at 190 degrees C was observed. In contrast, the distannoxane catalyst caused comparatively less transesterification reaction, and the randomization of the stereosequences was slow even at 190 degrees C. The L-lactic acid and D-lactic acid isomers were added to the polymer chain in a small, blocky fashion. The MALDI-TOF spectra of poly(L-lactic acid) (PLA) chains doped with Na+ and K+ cations showed that the PLA chains had the expected end groups. The MALDI-TOF analysis also enabled the simultaneous detection of the cyclic oligomers of PLA present in these samples, and this led to the full structural characterization of the molecular species in PIA. (c) 2005 Wiley Periodicals, Inc.
Keywords: C-13 NMR; dehydropolycondensation; Lewis acid catalysts; MALDI; polymerization; randomization; stereosequence

Sustainable materials based on aliphatic polyesters: teaching old chemistry some new tricks - Sivaram, S. (Current Science, 2013)

Synthesis of functional polymers of polar and nonpolar monomers by living and/or controlled polymerization - Chowdhury, S. R.; Sivaram, S. (Functional polymers: design, synthesis, and applications, 2017)